2013
DOI: 10.1111/1574-6941.12170
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and early succession of bacterial communities in monochloramine-treated drinking water biofilms

Abstract: Monochloramine is an increasingly used drinking water disinfectant and has been shown to increase nitrifying bacteria and mycobacteria in drinking waters. The potential successions and development of these bacteria were examined by 16S rRNA gene clone libraries generated from various biofilms within a water distribution system simulator. Biofilms were obtained from in-line and off-line devices using borosilicate glass beads, along with polycarbonate coupons from annular reactors incubated for up to 8 months in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 64 publications
8
44
0
Order By: Relevance
“…Firmicutes has usually been found to be a minor component of DWDS bacterial communities in both in bulk waters (Kormas et al, 2010;Lu et al, 2013;Pinto et al, 2012;Vaz-Moreira et al, 2013), and biofilms (Lin et al, 2013;Liu et al, 2014;Revetta et al, 2013). Our previous study showed that Firmicutes was usually a rare species in pipe biofilms from a real urban DWDS, while in few cases it could be a major component of biofilm bacterial community (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Firmicutes has usually been found to be a minor component of DWDS bacterial communities in both in bulk waters (Kormas et al, 2010;Lu et al, 2013;Pinto et al, 2012;Vaz-Moreira et al, 2013), and biofilms (Lin et al, 2013;Liu et al, 2014;Revetta et al, 2013). Our previous study showed that Firmicutes was usually a rare species in pipe biofilms from a real urban DWDS, while in few cases it could be a major component of biofilm bacterial community (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Primary succession in microbial communities has been investigated along receding glacier forelands (20,(23)(24)(25)(26)(27), in drinking water biofilms (17,(28)(29)(30), and in the rhizosphere (31)(32)(33)(34). These studies have collectively revealed a broad suite of patterns associated with shifts in community biomass, diversity, and composition, but none has directly characterized shifts in community assembly processes during succession.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Previous studies have shown that several organisms associated with DWDS can tolerate the effects of disinfectant compounds because of their ability to form biofilms (4,5). Unlike planktonic forms, bacteria in biofilms are more resistant to sterilization procedures and antimicrobial exposure, showing in some cases a MIC up to 1,000-fold higher than that of their planktonic counterparts (6).…”
mentioning
confidence: 99%